2019
DOI: 10.1002/ajs4.97
|View full text |Cite
|
Sign up to set email alerts
|

Conditionality in the context of housing‐led homelessness policy: Comparing Australia’s Housing First agenda to Scotland’s “rights‐based” approach

Abstract: Homelessness services and policy have historically tended to be organised by an explicitly conditional logic, wherein people experiencing homelessness must prove their “housing readiness” before accessing settled housing. This model has been robustly challenged in recent decades by “housing‐led” approaches that ostensibly eschew conditionality and prioritise the rapid rehousing of people experiencing homelessness. Various countries now include housing‐led approaches in the national policy frameworks, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
(41 reference statements)
1
20
0
Order By: Relevance
“…Our linked data analysis indicates a strong correlation between the volume and frequency of service contacts and the risk of housing insecurity. This finding is consistent with national and international reports that have consistently found that frequency and volume of service useage, particularly for mental health, housing and/or substance use services, predicts housing insecurity across the lifecourse (see Aubry, Goering et al 2016;Clarke, Watts et al 2020;Dunt, Benoy et al 2017: Hanratty, Miller et al 2020. Our data confirm that service transitions can have a significant impact on housing trajectories, particularly for vulnerable individuals with complex needs.…”
Section: How Does Residential Treatment Affect Individual Housing Careers Overtime?supporting
confidence: 91%
See 1 more Smart Citation
“…Our linked data analysis indicates a strong correlation between the volume and frequency of service contacts and the risk of housing insecurity. This finding is consistent with national and international reports that have consistently found that frequency and volume of service useage, particularly for mental health, housing and/or substance use services, predicts housing insecurity across the lifecourse (see Aubry, Goering et al 2016;Clarke, Watts et al 2020;Dunt, Benoy et al 2017: Hanratty, Miller et al 2020. Our data confirm that service transitions can have a significant impact on housing trajectories, particularly for vulnerable individuals with complex needs.…”
Section: How Does Residential Treatment Affect Individual Housing Careers Overtime?supporting
confidence: 91%
“…Of particular relevance to the analysis presented in this chapter, housing support services in Victoria and New South Wales have become increasingly complex in recent decades, with greater service specialisation involving more targeted policy supports, typically calibrated to address the needs of increasingly diverse groups (Brackertz, Davidson et al 2019;Parkinson and Parsell 2018). As housing, health and social care systems have been reformed and restructured in each jurisdiction, they have become more complex, more specialised and almost inevitably more difficult to navigate for vulnerable individuals (see Clarke, Watts et al 2020;Sylvestre, Nelson et al 2017).…”
Section: Integrating Housing Health and Social Carementioning
confidence: 99%
“…Globally, understandings of "what works" in responding to homelessness are at a critical moment. While traditional responses requiring people to navigate transitional and often congregate forms of accommodation, like hostels, still dominate (Mackie, Johnsen, and Wood 2017), there is a growing recognition that preventative and rapid-rehousing approaches are more effective in resolving homelessness and minimizing its ill effects (Culhane, Metraux, and Byrne 2011;Clarke, Watts, and Parsell 2020). Key here has been a fast-growing body of evidence on the Housing First model (Woodhall-Melnik and Dunn 2016), as well as the array of research detailing the negative experiences associated with hostels and other forms of congregate accommodation (Mackie, Johnsen, and Wood 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They conclude that neither system can claim to have integrity if they fail to embody their own concept of mutual obligation by upholding their duties to welfare recipients. Clarke et al (2020) aim to demonstrate the operations of conditionality in homelessness services and policy, and how conditional approaches have been challenged through recent policy and social change. They pursue this through a comparison of Scotland and Australia.…”
mentioning
confidence: 99%
“…Clarke et al () aim to demonstrate the operations of conditionality in homelessness services and policy, and how conditional approaches have been challenged through recent policy and social change. They pursue this through a comparison of Scotland and Australia.…”
mentioning
confidence: 99%